Subtitling Strategies and Translation Quality in Indonesian Fan Subtitle of Kung Fu Panda 4 - Ayuni Falhi, Qory; Widhiyanto; Haryanti, Rahayu Puji (LPPM Universitas Advent Indonesia, 2025)
This study investigates the balance between naturalness and accuracy in the Indonesian fan-sub of Kung Fu Panda 4. It examines the subtitling strategies employed by fan translators, utilizing Gottlieb’s (1992) subtitling strategies and Larson’s (1984) principles of translation quality. Adopting a descriptive qualitative approach, the research analyzed 139 lines from the movie, focusing on their cultural and linguistic complexity. The findings reveal that paraphrasing was the most frequently applied strategy (63.31%), followed by transfer (15.11%), expansion (9.35%), condensation (7.91%), and imitation (4.32%). These strategies enabled fan translators to adapt the source text while preserving its meaning, ensuring the subtitles were culturally and linguistically suitable for the Indonesian audience. Most subtitles were rated as moderately natural (79.86%) and moderately accurate (50.36%), with a smaller portion achieving high ratings. The study underscores the need to enhance naturalness and accuracy while emphasizing the importance of incorporating subtitling strategies in translation education to address real-world challenges.